2007
DOI: 10.1111/j.1365-3164.2007.00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Pradofloxacin in the treatment of canine deep pyoderma: a multicentred, blinded, randomized parallel trial

Abstract: A multicentre, randomized, blinded study compared the efficacy of pradofloxacin with that of a combination of amoxycillin/clavulanic acid in the treatment of deep pyoderma in dogs. Dogs with clinical lesions of deep pyoderma and a positive bacterial culture were included in the study. At each visit, they were evaluated with lesion, pruritus and general condition scores. Dogs were treated either with pradofloxacin at 3 mg kg-1 once daily or with amoxycillin at 10 mg kg-1 and clavulanic acid at 2.5 mg kg-1 twice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 16 publications
2
48
0
2
Order By: Relevance
“…Although it is not globally available at this time, a dualtargeting (both topoisomerase IV and DNA gyrase), thirdgeneration fluoroquinolone, pradofloxacin, has shown superior activity in terms of both lower MPC values than other veterinary fluoroquinolones (Wetzstein, 2005) and clinical efficacy against various infections, including UTIs in cats (Litster et al, 2007) and canine pyoderma (Mueller & Stephan, 2007). It has already been suggested that the introduction into the veterinary market of such agents that combine high therapeutic efficacy with a high potential for restricting the selection for fluoroquinolone resistance would promote rational antibacterial-drug therapy in companion animals (Wetzstein, 2005;Litster et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is not globally available at this time, a dualtargeting (both topoisomerase IV and DNA gyrase), thirdgeneration fluoroquinolone, pradofloxacin, has shown superior activity in terms of both lower MPC values than other veterinary fluoroquinolones (Wetzstein, 2005) and clinical efficacy against various infections, including UTIs in cats (Litster et al, 2007) and canine pyoderma (Mueller & Stephan, 2007). It has already been suggested that the introduction into the veterinary market of such agents that combine high therapeutic efficacy with a high potential for restricting the selection for fluoroquinolone resistance would promote rational antibacterial-drug therapy in companion animals (Wetzstein, 2005;Litster et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli is the predominant cause of urinary tract infections (UTIs) in both dogs and cats, and is also isolated frequently from contaminated wounds, surgical infections of the skin and adjacent soft tissues, and deep canine pyodermas (Booth, 2001;Mueller & Stephan, 2007). Although fluoroquinolones belong to one of the most useful classes of antimicrobial agents used to combat various infections, including those caused by E. coli, resistance in canine E. coli isolates to a wide range of fluoroquinolones is increasingly reported (Cohn et al, 2003;Ball et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Pradofloxacin is a new compound developed for the management of bacterial infections in dogs and cats, which has been shown to have the highest therapeutic efficacy combined with high potential for restricting the emergence of resistance in comparison with other six veterinary FQs in vitro [4], and a recent multicentre study in vivo showed that pradofloxacin has an efficacious therapy comparable to amoxycillin/clavulanic acid for deep bacterial pyoderma in dogs [5].…”
Section: Introductionmentioning
confidence: 99%
“…Deep pyoderma, which is often associated with cellulitis, can be difficult to treat because bacteria in lesions are often in the centre of inflammatory foci (Mueller & Stephan, 2007). Pyoderma is mainly caused by Gram‐positive bacteria (most notably coagulase‐positive and coagulase‐negative staphylococci) but also by Gram‐negative bacteria such as Pseudomonas aeruginosa and Escherichia coli (Mueller & Stephan, 2007). The most important pathogen associated with canine pyoderma is Staphylococcus pseudintermedius, a resident of the normal skin (Fitzgerald, 2009).…”
Section: Introductionmentioning
confidence: 99%